Key mineral materials for the development of the green economy in Peru - Faustino Luis, Hugo Simon (2023)
Concern about reducing greenhouse gases drives us to migrate to the use of clean energy. Therefore, a large investment in the green economy modality is necessary, since the brown economy does not include sustainable development (Campos, 2010). When we talk about the economy in Peru, it is important to mention mining and its benefits, not only economic, but also environmental. The article aims to investigate and highlight the importance of mining as a driver of the green economy, this from the point of view of its minerals. A clear example of this are critical minerals such as lithium, cobalt, nickel, silver, and tungsten, crucial in the manufacture of new clean technologies. So also, minerals, which, indirectly, are necessary in the infrastructure, such as copper, iron, aluminum, steel; These are characterized by their durability and, in cases such as copper, being 100% recyclable. This is how Peru is one of the countries with the best prospecting in mining (Cooke, 2021), either in the field of critical minerals with the potential of its deposits and with infrastructure minerals, which are currently maintained by the economy. from the country.